The ESCRT complexes: methods and protocols - Culetto, Emmanuel; Legouis, Renaud (Methods in molecular biology, 2019)
Analysis of the Archaeal ESCRT Apparatus -- Genetic and Cell Biology Methods to Study ESCRTs in Drosophila melanogaster -- Functional Analysis of ESCRT-Positive Extracellular Vesicles in the Drosophila Wing Imaginal Disc -- Subcellular Localization of ESCRT-II in the Nematode C. elegans by Correlative-Light Electron Microscopy -- Proximity Ligation Assay (PLA) to Determine the Endosomal Localization of ESCRT Subunit in Virus-Infected Cells -- Immuno-Localization of ESCRT Proteins in Virus-Infected Cells by Fluorescence and Electron Microscopy -- Single Cell Fluorescence Ratio Image Analysis for Studying ESCRT Function in Receptor Trafficking -- Genetic and Biochemical Analyses of Yeast ESCRT -- Live Imaging of ESCRT Proteins in Microfluidically-Isolated Hippocampal Axons -- Studying the Spatial Organization of ESCRTs in Cytokinetic Abscission Using the High Resolution Imaging Techniques SIM and Cryo-SXT -- Three Dimensional Surface Rendering of ESCRT Proteins Microscopy Data Using UCSF Chimera Software -- Transient Expression of ESCRT-Components in Arabidopsis Root Cell Suspension Culture-Derived Protoplasts -- Crystallization and Biophysical Approaches for Studying the Interactions between the Vps4-MIT Domain and ESCRT-III Proteins -- Biochemical Approaches to Studying C. elegans ESCRT Function In Vitro -- Purification of Recombinant ESCRT-III Proteins and Their Use in Atomic Force Microscopy and In Vitro Binding and Phosphorylation Assays -- Assessment of ESCRT Protein CHMP5 Activity on Client Protein Ubiquitination by Immunoprecipitation and Western Blotting -- Purification of Plant ESCRT Proteins for Polyclonal Antibody Production -- Genetic and Cytological Methods to Study ESCRT Cell Cycle Function in Fission Yeast -- ESCRT Mutant Analysis and Imaging of ESCRT Components in the Model Fungus Ustilago maydis -- Genetic Suppressor Screen Using an Inducible FREE1-RNAi Line to Detect ESCRT Genetic Interactors in Arabidopsis thaliana -- Screening of Interactions with the ESCRT Machinery by a Gaussia princeps Split Luciferase-Based Complementation Assay -- RNA Interference-Mediated Inhibition of ESCRT in Mammalian Cells